The Transformative Role of Artificial Intelligence in Education Pathways to Viksit Bharat 2047 - Hanumantha V. Ninganagowdar (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
The Article discusses how Artificial Intelligence (AI) can revolutionize Indian education to achieve the "Viksit Bharat 2047" vision by creating personalized, accessible, and effective learning experiences. AI can help bridge the digital divide, boost administrative efficiency, and foster a skilled workforce through adaptive learning platforms and data-driven insights. However, the abstract also emphasizes the importance of addressing ethical challenges and ensuring equitable access to harness AI’s potential for inclusive and transformative growth.